Project-Based Versus Traditional Lecture Teaching Methods - Muhammad Hafeez (Future Science, 2021)
To compete with the world in the 21st century, it is necessary to adopt modern learning strategies like inquiry-based, project-based, problem-based. The traditional learning strategies are no viable now to improve the learning skills of the learners. A review of previous studies on traditional lecture-based and project-based learning strategies has been conducted to evaluate the effectiveness of both learning strategies. The learning outcomes and statistical results of 15 previously published articles have been selected for this review study. The learning outcomes and statistical results of previous literature indicated that all the studies showed significant improvement in the learning and cognitive skills of the learners. The effectiveness of project-based teaching strategy in various educational levels are also described in the study.